(untitled) (Archives of Pediatrics of Uruguay, 2025)
Arterial hypertension (AH) is an increasing trend in pediatrics. Timely diagnosis and treatment can help identify underlying causes and prevent both acute and long-term complications. Pheochromocytomas and paragangliomas are rare causes of AH in children. The objective is to report a case of AH secondary to a genetically determined pheochromocytoma, associated with ipsilateral renal atrophy. We present the case of a 9-year-old asymptomatic school-age girl with severe chronic AH, normal kidney function, and no target organ damage. Ultrasound and angiography revealed a nodule in the right adrenal topography. A DMSA scan showed 12% uptake in the right kidney. Urinary metanephrines and renin levels were markedly elevated. PET confirmed the presence of a pheochromocytoma without dissemination. After a gradual decrease in blood pressure, surgical resection was performed. Histopathological analysis confirmed the diagnosis and its benign nature. Genetic testing identified the pathogenic variant c.72+1G>A in the SDHB gene. Postoperatively, AH persisted, but metanephrine levels normalized. Doppler ultrasound showed hypovascularization in the upper half of the kidney, and DMSA uptake decreased to 9%. A nephrectomy was performed. Blood pressure normalized in the office setting, but ambulatory blood pressure monitoring remained abnormal. Multidisciplinary follow-up is essential for this monorenal patient, who presents with masked AH and remains at risk for tumor recurrence and malignancy.